1997
DOI: 10.1111/j.1600-0749.1997.tb00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Pathological, and Etiologic Aspects of Acquired Dermal Melanocytosis

Abstract: To study the pathogenesis of acquired dermal melanocytosis (ADM), we reviewed the clinical, immunohistochemical, and ultrastructural features of 34 cases (female, 33, and male, 1) of ADM. The patients' ages at onset ranged from 8 to 51 years and averaged 26.8 +/- 12.7 years. There was a positive family history. Gray-brown macules were mostly recognized on the face. Not only active dermal melanocytes but also non-pigmented c-KIT- and TRP-2-positive immature melanocytes were detected in the dermis. Taken togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 8 publications
1
41
0
1
Order By: Relevance
“…Extra-facial lesions are rare but can occur on the back, limbs, or extremities. [10][11][12][13] It is unclear whether the extra-facial condition is a separate entity from acquired bilateral nevus of Ota-like macules. A previous study found no significant difference in the histopathological features of facial and extra-facial lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Extra-facial lesions are rare but can occur on the back, limbs, or extremities. [10][11][12][13] It is unclear whether the extra-facial condition is a separate entity from acquired bilateral nevus of Ota-like macules. A previous study found no significant difference in the histopathological features of facial and extra-facial lesions.…”
Section: Discussionmentioning
confidence: 98%
“…In acquired dermal melanocytosis, the fully pigmented dendrites of dermal melanocytes embracing elastic fibers, but without evidence of phagocytosis of these fibers. Furthermore, non-pigmented c-kit-and/or TRP-2-positive immature melanocytes were found in the dermis of the lesions, which implied there were preexisting immature melanocytes and through some factors' activation, they became differentiated to produce pigment [2]. Based on these findings we hypothesize that elastic fibers may play a role in regulating the development of melanocyte precursors.…”
Section: Introductionmentioning
confidence: 88%
“…Spindle-shaped c-kit-positive melanocytes with brown granules are evident in the middle and upper dermis 33 (in contrast to Ota nevus, which has melanocytes in the upper and lower dermis). In the ultrastructural study, melanosomes are in stages II-IV of melanization, 28 mostly in stage IV.…”
Section: Morphologymentioning
confidence: 96%
“…Synonyms for Hori nevus and Sun nevus: naevus fuscocaeruleus zygomaticus 31 ; acquired dermal melanocytosis 29,33 ; acquired bilateral nevus of Ota-like macules 34,35 ; acquired symmetrical dermal melanocytosis. 29 Synonyms for Hidanos nevus: acquired dermal melanocytosis of the face and extremities.…”
Section: Synonymsmentioning
confidence: 99%